A sulfur dioxide detection platform based on photoacoustic spectroscopy and a 266.22 nm high-power stabilized LD-pumped solid-state Q-switched laser - Xiaowen Shen; Yixin Zhang; Ruyue Cui; Donghe Tian; Ming Cheng; Pietro Patimisco; Angelo Sampaolo; Chaofeng Sun; Xukun Yin; Vincenzo Spagnolo; Lei Dong; Hongpeng Wu (Photoacoustics)
A ppb-level sulfur dioxide (SO2) monitoring platform was developed by exploiting standard photoacoustic spectroscopy and a novel, highly stable UV laser. A 266.22 nm LD-pumped solid-state, acousto-optic modulator Q-switched laser with high beam quality (M2 =1.0275) and excellent output optical power stability (δPσ ˂ 1 % ∼24 h) was selected as light source of the photoacoustic sensor. The performance of the SO2 sensor was evaluated in terms of gas flow rate, pressure, and detection sensitivity. An ultimate detection limit of 3 ppb for SO2 detection in N2 was demonstrated with 1 s integration time, in laboratory environment. Continuous outdoor monitoring for five days verified the excellent stability and reliability of the reported SO2 photoacoustic sensor.